Relationship between Motivation Following Prolanis Gymnastics and the Risk of Diabetes Mellitus Recurrence - Rahma, Marliana; Syamsiyah, Nita (Jurnal Midpro, 2020)
The study, entitled The Relationship to Understanding Gymnastics, Prolanis and the Risk of Diabetes Mellitus Recurrence, aims to analyze the intelligence of Prolanis Gymnastics Proclamation with the Risk of Recurrence in Type II Diabetes Mellitus Patients in the Muaragembong Community Health Center Work Area.Method: This research is a quantitative study using a descriptive correlational design, the design used in this study is a design to examine the relationship between two variables in the study or a combination of subjects. Factors that influence, special events that arise related to the case. By discussing cross-sectional research is conducted in which both dependent variables are independent at the same timeResults: General description of the majority of respondents 45-50 years old respondents, most respondents were housewives, the most recent education had a level of education not schooling and gender respondents were supported by women as much as 76.9%. most of the motivations are good. General description The risk of recurrence is that most respondents are good. Chi square research results There is a correlation Motivation to take Prolanis exercises with the risk of recurrence in the sense that means the better motivation in following Prolanis exercises, the better the Diabetes Mellitus patients to the risk of recurrence.Â Â